ChemInform Abstract: Iron‐Catalyzed Regioselective Direct Arylation at the C‐3 Position of N‐Alkyl‐2‐pyridone. Issue 21 (May 2015) - Modak, Atanu; Rana, Sujoy; Maiti, Debabrata
Abstract C‐3‐arylated 2‐pyridones are synthesized by direct C‐H coupling of the corresponding N‐alkyl‐2‐pyridones with arylboronic acids using potassium peroxodisulfate as oxidant in the presence of Fe(III)‐catalyst.